A two-port antenna for wireless-powered UWB-RFID tags - Shen, Yizhu (2013)
This paper presents a two-port antenna including a receiving port and a transmitting one in the same volume. These two antennas are physically integrated and electrically isolated. The receiving antenna is a linearly polarized narrowband slot for energy harvesting, whereas the transmitting one is a circularly-polarized ultrawideband (UWB) quasi-spiral for signal radiation. The measurement results show that, the slot resonates at 5.8 GHz, and the quasi-spiral has a 10-dB return loss bandwidth of 2.85-5.16 GHz and a 3-dB axial ratio bandwidth of 3.05-4.43 GHz. The electrical isolation between these two antennas is more than 20 dB covering 1-8 GHz. This two-port antenna is a good candidate for wireless-powered UWB-RFID tags.